2006
DOI: 10.1111/j.1442-200x.2006.02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory inhibition after crying in infants

Abstract: Respiratory inhibition after crying which involved a marked decrease in SpO2 was observed in full-term neonates who showed no abnormalities after birth. These neonates could be screened by cranial ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
(5 reference statements)
1
10
1
Order By: Relevance
“…In the present study, as in our previous studies, 1,2 we found a significant correlation between RIAC and increased echogenicity in the GE. Among 67 infants with increased echogenicity in the GE, 48 showed increased echogenicity on the day of admission to our NICU.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, as in our previous studies, 1,2 we found a significant correlation between RIAC and increased echogenicity in the GE. Among 67 infants with increased echogenicity in the GE, 48 showed increased echogenicity on the day of admission to our NICU.…”
Section: Discussionsupporting
confidence: 92%
“…We previously examined infants who showed a respiratory pause immediately after crying associated with a marked decrease in oxygen saturation (SpO 2 ), and termed this phenomenon “respiratory inhibition after crying (RIAC).” 1 We observed RIAC in full‐term infants who had no obvious abnormalities during gestation and labor. The majority of infants with RIAC show the frequent occurrence of a respiratory pause on initiation of feeding immediately after crying with a decrease in SpO 2 to <80%; we termed this phenomenon “feeding hypoxemia.” We established an effective screening method for RIAC using cranial ultrasound and SpO 2 monitoring 2 .…”
mentioning
confidence: 99%
“…Increased echogenicity in the GE was observed persistently until the anterior fontanel closed. It could not be detected on computed tomography or magnetic resonance imaging 1 . In the present study, all infants had ultrasound abnormalities in the GE on the day of birth.…”
Section: Discussioncontrasting
confidence: 57%
“…We first identified an infant with RIAC in 2001 1 . The respiratory state of this infant while quiet or sleeping was very stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation